Ecological States Politics of Science and Nature in Urbanizing China - Rodenbiker, Jesse (Cornell University Press, 2023)
Ecological States critically examines ecological policies in the People's Republic of China to show how campaigns of scientifically based environmental protection transform nature and society. While many point to China's ecological civilization programs as a new paradigm for global environmental governance, Jesse Rodenbiker argues that ecological redlining extends the reach of the authoritarian state. Although Chinese urban sustainability initiatives have driven millions of citizens from their land and housing, Rodenbiker shows that these migrants are not passive subjects of state policy. Instead, they creatively navigate resettlement processes in pursuit of their own benefit. However, their resistance is limited by varied forms of state-backed infrastructural violence. Through extensive fieldwork with scientists, urban planners, and everyday citizens in southwestern China, Ecological States exposes the ways in which the scientific logics and practices fundamental to China's green urbanization have solidified state power and contributed to dispossession and social inequality This book is freely available in an open access edition through the generous support of the Henry Luce Foundation.